(untitled) (TEST Ticontre. Theory Text Translation, 2017)
Self-translation is regarded by scholars in the field of Translation Studies as an activity undertaken by many writers from different literature and language backgrounds. Also, it is described as an area of translation studies that so far has been almost forgotten. We have chosen to focus our attention on the instances of autobiographical texts produced by exiles, on exile itself as a factor that leads writers into self-translation and on the instruments used by exiled writers for self-promotion. We have chosen to focus our analysis on the trajectories of Gustavo Pérez Firmat and Ariel Dorfman, writers and self-translators with at least three characteristics in common: they are Latin-American writers; they have chosen to live in the USA; they have translated their autobiographies into Spanish, their native tongue. However, self-translation is not the only instrument of promotion “chosen” by Pérez Firmat and Dorfman. They also act as university professors, scholars, essayists, human rights activists, speakers, and editors to produce different instances of autobiographical texts, which represent powerful tools for self promotion. Finally, we will focus on Pérez Firmat’s and Dorfman’s autobiographies so as to explore how their lives in-between languages is made explicit in the text they write and self-translate. We hope to shed light on self-translation, on exile as a factor that affects self-translation and on the instruments used by writers to reinvent themselves in a foreign country. KEY WORDS: AUTOBIOGRAPHY, SELF-TRANSLATION, LANGUAGE, EXILE, SELF-TRANSLATORS, SELF-PROMOTION, AUTOBIOGRAPHICAL TEXTS